Integrated Analysis of mRNA-Seq and MiRNA-Seq Reveals the Molecular Mechanism of the Intestinal Immune Response in Marsupenaeus japonicus Under Decapod Iridescent Virus 1 Infection - He, Zihao; Zhong, Yunqi; Hou, Danqing; Hu, Xianye; Fu, Zhibin; Liu, Luyao; Zhang, Shuang; Sun, Chengbo (Frontiers in Immunology, 2022)
The intestine is not only an important digestive organ, but also an important immune organ of shrimp, which plays a key role in maintaining homeostasis. Decapod iridescent virus 1(DIV1) is a new type of shrimp lethal virus, which has received extensive attention in recent years. Up to now, most of the studies on shrimp intestinal immune response under viral infections mainly rely on single omics for analysis, and lack of multi-omics systematic research. In the current study, the intestinal mRNA-seq and miRNA-seq of Marsupenaeus japonicus under DIV1 infection were jointly analyzed. A total of 1,976 differentially expressed genes (DEGs) and 32 differentially expressed miRNAs (DEMs) were identified. Among of them, 21 DEMs were negatively correlated with 194 DEGs, and there were a total of 223 correlation numbers. Through the functional annotation analysis, the results revealed that M. japonicus could regulate glycosaminoglycan biosynthesis (chondroitin sulfate, dermatan sulfate and keratan sulfate), vitamin metabolism (Retinol metabolism and Ascorbate and aldarate metabolism), immune pathway activation (Toll and IMD signaling pathway, Wnt signaling pathway, IL-17 signaling pathway and Hippo signaling pathway), immunity enzyme activity promotion (triose-phosphate isomerase), AMPs expression, ROS production and cell apoptosis through miRNAs to participate in the host’s antiviral immune response, while DIV1 could influence the Warburg effect-related pathways (Pyruvate metabolism, Glycolysis / Gluconeogenesis and Citrate cycle), glycosphingolipid biosynthesis-related pathways (Glycosphingolipid biosynthesis - globo and isoglobo series and Glycosphingolipid biosynthesis - lacto and neolacto series) and tight junction and adhesion junction of the intestinal mucosal epithelium through host’s miRNAs and mRNA to promote its own invasion and replication. These reuslts indicated that intestinal miRNAs played an important role in shrimp against DIV1 infection, which provided information for further study of shrimp intestinal antiviral immune response and helped formulate effective new strategies for the prevention and treatment of DIV1 infection.